P2-118. Clinical electroencephalographic study in ten cases with Posterior Reversible Encephalopathy Syndrome (PRES). Issue 9 (September 2017) - Ohfu, Masaharu; Matsuoka, Tsuyoshi; Hiyane, Masato
Abstract : Posterior reversible encephalopathy syndrome (PRES) is firstly a reversible vasogenic edema derived from vascular endothelial dysfunction and elevation of blood pressure but is finally an irreversible cytotoxic edema. We retrospectively assessed medical charts and EEG and MRI studies of ten child patients with PRES treated between 2008 and 2015. Onset age are 4–9 (mean 6) year of age. The underlying disorders were hemato-oncologic disease in 5, nephrotic syndrome in 5, Henoch-schonlein purpura in 1 and chronic EBV infection in 1. EEG showed PLEDs (Periodic Lateralized Epileptic Discharges) in 6, diffuse irregular slow in1, normal in 3. MRI of PLEDs group revealed all cytotoxic edema as high signal on DWI and low signal on ADC map. MRI of others showed vasogenic edema as low signal on DWI and high signal on ADC map or only high signal on FLAIR image. All had recovered under regulation of blood pressure. We observed high frequently PLEDs on acute stage and MRI shows cytotoxic edema. By contrast, those who showed vasogenic edema on MRI had no PLEDs. It seemed that presence of PLEDs indicate severity of cell damages. PLEDs sign indicate as a marker of cytotoxic edema on PRES.